APPLICATION OF FIFO ALGORITHM (FIRST IN FIRST OUT) TO SIMULATION QUEUE - Jonson Manurung (INFOKUM, 2019)
In everyday life, many activities are found. One of them is waiting in line. Queuing is a boring thing. Moreover, the arrangement of the queues is not organized and the officers do not pay attention to who is the first to queue. So it is not uncommon to cause complications and even angry. Therefore, to handle problems in the queue, the simulation is implemented using the first in first out algorithm. With this algorithm, it can help determine who will be served first. Simulation is a way that is done to apply a more realistic system estimate. In this case, the authors use the first in first out algorithm. First in first out algorithm, i.e. first in, first out. In this case who is the first to wait in line, he will be served first and finish first. In this way, it is hoped that this will help determine who will be served first.